Self-consistent approach for Bose-condensed atoms in optical lattices - Yukalov, V.I. (Condensed Matter Physics, 2013)
Bose atoms in optical lattices are considered at low temperatures and weak interactions, when Bose-Einstein condensate is formed. A self-consistent approach, based on the use of a representative statistical ensemble, is employed, guaranteeing a gapless spectrum of collective excitations and the validity of conservation laws. In order to show that the approach is applicable to both weak and tight binding, the problem is treated in the Bloch as well as in the Wannier representations. Both these ways result in similar expressions that are compared for the self-consistent Hartree-Fock-Bogolubov approximation. A convenient general formula for the superfluid fraction of atoms in an optical lattice is derived. Розглядаються атоми Бозе в оптичних гратках при низьких температурах i слабких взаємодiях, коли кон-денсат Бозе-Ейнштейна є утворений. Застосовано самоузгоджений пiдхiд, що базується на використаннi репрезентативного статистичного ансамблю i забезпечує безщiлинний спектр колективних збуджень i чиннiсть законiв збереження. Для того, щоб показати застосовнiсть пiдходу до обох, слабкого i сильного зв’язку, проблема розглядається в представленнях Блоха i Ваньє. Обидва способи приводять до подiбних виразiв, що порiвнюються з самоузгодженим наближенням Хартрi-Фока-Боголюбова. Отримано зручну загальну формулу для надплинної фракцiї атомiв в оптичнiй гратцi.